Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1038/ajg.2014.232
|View full text |Cite
|
Sign up to set email alerts
|

What Level of Bowel Prep Quality Requires Early Repeat Colonoscopy: Systematic Review and Meta-Analysis of the Impact of Preparation Quality on Adenoma Detection Rate

Abstract: OBJECTIVES Current guidelines recommend early repeat colonoscopy when bowel preparation quality is inadequate, defined as inability to detect polyps > 5 mm, but no data link specific bowel preparation categories or scores to this definition. Nevertheless, most physicians use a shortened screening/surveillance interval in patients with intermediate-quality preparation. We determined whether different levels of bowel preparation quality are associated with differences in adenoma detection rates (ADRs: proportion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
186
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(203 citation statements)
references
References 35 publications
7
186
0
5
Order By: Relevance
“…Inadequate bowel preparation is associated with missed lesions, repeated colonoscopy, and higher adverse event rate (12,13). Various methods have been proposed to improve the quality of bowel preparation (14-16), nonetheless, suboptimal bowel preparation is still commonly encountered in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate bowel preparation is associated with missed lesions, repeated colonoscopy, and higher adverse event rate (12,13). Various methods have been proposed to improve the quality of bowel preparation (14-16), nonetheless, suboptimal bowel preparation is still commonly encountered in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…There is only weak evidence on how to salvage a procedure when bowel preparation is found to be inadequate. 61 However, the importance of achieving good bowel preparation cannot be overstated; a systematic review 62 found that adenoma detection rates were significantly higher in patients with adequate or good-quality preparation compared with poor-quality preparation.…”
Section: Examination Qualitymentioning
confidence: 99%
“…8 A recent systematic review and meta-analysis of 11 studies observed no difference in adenoma detection rate (ADR) between examinations with intermediate-quality (fair) compared with those with high-quality preparation (good or excellent) (odds ratio [OR], 0.94; 95% confidence interval [CI], 0.80, 1.10). 9 In contrast, ADRs were significantly higher with both intermediate-quality (OR, 1.39; 95% CI, 1.08, 1.79) and high-quality preparations (OR, 1.41; 95% CI, 1.21, 1.64) compared with low-quality (poor) preparations. Similar findings were observed in an analysis of 13,000 colonoscopies within a statewide registry, with comparable ADRs in examinations with fair-quality versus optimalquality preparation.…”
Section: Bowel Preparation and Its Impact On Colonoscopy Qualitymentioning
confidence: 73%